Sosialisasi Inovasi Pembayaran Digital WeChat Pay ke Generasi Z Universitas Esa Unggul dan President University - Ikramina Larasati Hazrati Havidz; Hernawati W. Retno Wiratih; M. Havidz Aima; Maya Puspita Dewi; Retnowati Retnowati (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Along with the development and innovation of technology information at the international level, one of the transactions payment is from offline to online (cashless payment).  The utilization of technology cashless platforms mobile payment, Indonesia, India, the Philippines, Malaysia, and Singapore still shows less than 4%. In Indonesia, there are currently 21 companies (providers) that are engaged in mobile payment with a variety of services provided. Millennial, Generation-Z, tends to have a virtual transaction space that has attracted their interest in using social media as a technology with cashless payments of We-Chat pay. At the end of the activity, a post-test was held relates to the socialization of the We-Chat Pay as one of Digital Payment Innovation. The posttest was given to find out the enthusiasm of the participants. The post-test obtained an overview of the participants’ interest in the use of We-Chat pay cashless payments, namely 34% as an option for shopping; 30% as an option to eat together; 19% as an option for traveling; and 17% as an option for Nobar (watching together). Therefore, it does not rule out the possibility of the digital payment technology apply in Jakarta and Bekasi, Indonesia to adopt the innovation of WeChat Pay.